(3ecGaMI GdGZQGb GdJLGQj (B:s (3GdJOGHjQ GdbGfhfjI aj GdbhGfjf h GdGJaGbjGJ GdOhdjI (B/s - (3GdMWGH, EjGO YUGes ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2011)
(3eaghe GdEZQGb h CfhGYg h TQhW JMbbg, GdGLQGAGJ h GdTQhW GdhGLH JWHjbgG decGaMI GdEZQGb aj GdbGfhf GdCQOfj h GdGJaGbjGJ GdOhdjI, GdCMcGe GdcajdI HecGaMI GdEZQGb aj GdbGfhf GdCQOfj h GdGJaGbjGJ GdOhdjIs
(3HHdjhZQGajG(B: (3U(B.263-279s
Keywords: (3GdGJaGbjGJ GdOhdjIs; (3GdEZQGb(B- (3GdJLGQIs; (3GdbGfhfs; (3GdbGfhf GdOhdjs